Real or False Image of Police Recorded Crime: What Do the Crime Data Show? - Stefanovska, Vesna (Kriminologija I Socijalna Integracija, 2019)
The process of police crime recording is a research issue in many studies within the expert and research community. Since police crime statistics are a product of police practice to record crime, the question how to measure, count and record all reported crimes in an objective and accurate manner includes serious challenges and weaknesses. In fact, the dominant view within social constructivism and critical theories is an institutional approach which means that police data on crime are suspicious and subject to manipulative practices by the police. The basis of this approach is the principle that crime statistics are subject to construction by the police and primarily serve to achieve certain organizational goals and priorities. This means that crime numbers do not reflect reality but represent its subjective reflection. In a way, they are a part of police gaming in recording and classifying reported events as a crime. The associated decision-making process is affected by different organisational, social and situational factors which can have influence on the crime rate, so the most frequent question remains whether the data show true or false picture of a crime. The answer depends on many factors: adoption of police recording standards to harmonize different police practices and to establish legal rules and guiding principles, determination of organizational goals and priorities within certain period, establishment of police performance indicators, cognitive and other capabilities of police officers etc. Those factors and possible techniques used by the police to manipulate crime recording in order to distort the real picture of reported crimes will be analysed within this paper. In fact, we will go through a certain manipulation process known as that police gaming in crime recording practices that is affected by different factors. We have divided these cases into three basis categories: legal framework for crime recording; police organizational structure and priorities and police discretionary practices. Our aim is to discuss possible obstacles and recent findings that prevent correct crime recording by the police which distort the real picture of a reported crime.